Setting up the framework of capacities for innovation of enterprises in actual context of Vietnam - Khiem, Vu Van; Phuong, Ho The Nam; Dung, Bui Tien (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
The article aims to build a framework for the capabilities of innovation in Vietnamese companies suitable to new conditions in Vietnam. The authors analyze currently the internal and external factors that influence the capacities for innovation of enterprises today. At the same time, based on the analysis of the core factors which compose the capacity of innovation, this research provides a framework for innovation of enterprises. Therefore this research sets the background for more in-depth studies orienting to enhance the capacity for innovation in various types of enterprises in Vietnam.